Utilization Of Agung Semeru Banana Peel Extract As Natural Hand Sanitizer - Dwi Nur Rikhma Sari; Septarini Dian Anitasari; Suci Ratnasari (Biota, 2020)
Hand sanitizers generally contain Ethyl Alcohol 62%, softener, moisturizer and anti-bacterial compounds such as tryclosan, glycerol, tannin, saponins and other antimicrobial agents. This study aimed to determine the effect of Agung Semeru banana peel extract as a natural hand sanitizer to inhibit fungal growth of Candida albicans. The antifungal activity test is carried out using the disk diffusion method. The use of this method is shown to measure the diameter of the area of ​​resistance that occurs around paper discs that already contain antifungal in accordance with the concentration in each treatment. The results showed that Agung Semeru banana peel is effective as a natural Hand sanitizer that was indicated by differences in treatment. Utilization of Agung Semeru Banana peel Extract as a natural basic material hand sanitizer showed that no significant difference between treatments in inhibiting the growth of fungi Candida albicans, but a concentration of 7% (1,315 ± 0.0035c) showed better results compared to a concentration of 1% ( 1.2 ± 0.0a); concentration of 5% (1,208 ± 0,0023b) and 0% (1.2 ± 0,0a).